Prevalence of sensorineural hearing loss in patients with head and neck malignancy who underwent chemotherapy and or radiotherapy - Jacob, Anu; Jino M., Erin; K. P., Gopakumar; Kumar, Chethan; T., Kiren (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Our study aimed to focus on the importance of the rate at which the sensory neural hearing loss (SNHL) is caused by chemotherapy (CT) and or radiotherapy (RT). This study also tells about the importance of informing the patient and the caretakers prior to the start of treatment for carcinoma, so that they can be prepared for it if it happens. Methods: Total 75 patients who were diagnosed to have any form of head and neck malignancy formed the study group. Pure tone audiometry was recorded pre-treatment, one month after treatment and six months after treatment. All the data obtained were bio statistically analysed by running in SPSS software version 26. Results: There is a correlation between CT, RT and concurrent chemo radiotherapy (CRT) and SNHL. It is also found that most of the patients who have undergone CRT suffered SNHL in the long run. Conclusions: It is high time the patients are made aware of the side effects like SNHL before the start of the proposed treatment. This will allow them to be prepared and then face it.